2006
DOI: 10.1128/jcm.01763-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Chromogenic Medium, MRSA Select , for Detection of Methicillin-Resistant Staphylococcus aureus

Abstract: We compared MRSA Select to mannitol-salt agar with 8 g/ml cefoxitin for the detection of methicillinresistant Staphylococcus aureus (MRSA) from 6,199 clinical samples submitted for MRSA screening. The sensitivities and specificities of MRSA Select and mannitol-salt agar with cefoxitin were 98% and 92% versus 90% and 78%, respectively (P < 0.0001). Most (96%) MRSA were detected after overnight incubation using MRSA Select.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…Van Hal et al (28,29), who used PCR detection of MRSA for comparison in two studies, found recovery rates of around 75% for the selective media. Groups that compared only one selective medium with nonselective media reported recovery rates above 90% (9,12,19,24,27). Hence, comparison of results gained from different studies can only be performed very cautiously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Van Hal et al (28,29), who used PCR detection of MRSA for comparison in two studies, found recovery rates of around 75% for the selective media. Groups that compared only one selective medium with nonselective media reported recovery rates above 90% (9,12,19,24,27). Hence, comparison of results gained from different studies can only be performed very cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the sensitivities of different chromogenic media may be caused by additives in the media that inhibit growth of the concomitant microorganisms but that also inhibit the growth of MRSA (25). However, groups that compared different media usually did not compare the recovery rates for different specimens on selective media to those on nonselective media (19,22,26,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, [9], [11,12] [7], [12,13] [9], [12] [6], [8][9][10][11][12] [6], [8,9], [11,12] [12] [7], [9][10][11], [13] [9], [11], [13] [9] [6,7], [9], [12,13] …”
mentioning
confidence: 99%